Peran internal public relations dalam meningkatkan kepatuhan syariah karyawan: studi kasus bank muamalat indonesia - Nurahmani, Marsheila Fithri Aisyah (Maliki Interdisciplinary Journal, 2025)
This article examines the strategic role of Internal Public Relations in enhancing employee Sharia compliance at Bank Muamalat Indonesia. Using a conceptual approach, this study examines the role of internal communication based on Islamic values ​​in building a religious work culture and integrity within the organization. Internal Public Relations not only serves to convey policy information but also serves as a means of da'wah that instills the values ​​of amanah, tabligh, and ihsan in the workplace. Research findings indicate that activities such as Sharia compliance training, regular discussions, and internal communication forums play a crucial role in enhancing employees' spiritual awareness and ethical responsibility. Good communication between management and employees can increase loyalty, transparency, and consistency in the implementation of Sharia principles. Internal Public Relations plays a key role in maintaining Islamic values ​​in Islamic financial institutions and ensuring the achievement of Sharia objectives (maqasid syariah) in banking activities.